RANCANG BANGUN SISTEM INFORMASI PARKIR MENGGUNAKAN LARAVEL 8 METODE WATERFALL DI INSTITUT TEKNOLOGI DAN BISNIS SWADHARMA - Gilang Salim; Muhammad Feizal (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Swadharma Institute of Technology and Business is one of the universities where parking system management is still carried out manually. Where every driver, whether students, lecturers and campus employees who want to enter and leave, is only carried out an inspection without a record. So that the entry and exit of two or four-wheeled vehicles is not recorded and controlled so that it is very possible for the crime of motor vehicle theft to occur. Based on the observations of the author trying to create an application that aims to regulate traffic entering and exiting vehicles in the parking area and facilitating parking data collection. This application uses the Waterfall method using the Laravel framework and the database used is MySql because the security system is more secure.